PEMBUATAN BRIKET ARANG DARI BLENDING CANGKANG KELAPA SAWIT DAN TONGKOL JAGUNG MENGGUNAKAN PEREKAT TAPIOKA - Afriedy Syaputra Siburian; Pada Mulia Raja; Busrizal Faisal; Fachrizal (Jurnal Agro Fabrica, 2024)
Briquettes are solid fuels made from a mixture of palm kernel shells and corn cobs. Usually used as an alternative fuel such as firewood, charcoal, or coal. This study aims to determine the best composition for briquette quality. Palm kernel shells are a by-product of palm oil processing, while corn cobs are the part of the corn plant at the top of the stem that functions as a place for corn kernels to grow. Corn cobs are often unused agricultural waste. The study was conducted at the ITSI Process Laboratory, ITSI Physics Laboratory, and PTKI Physics Laboratory with an experimental method using This study used the Completely Randomized Design (CRD) Non-Factorial method using three variations of Comparison (Palm Kernel Shells 75%: 25% Corn Cobs; Palm Kernel Shells 50%: 50% Corn Cobs; Palm Kernel Shells 25%: 75% Corn Cobs) with three repetitions each. With the addition of Tapoika each 20%.. High water content can affect the quality of briquettes, because it can inhibit the evaporation process, combustion, and density of briquettes.